DAMPAK PEMBANGUNAN WADUK KUWIL TERHADAP SOSIAL EKONOMI MASYARAKAT DI SEKITAR PEMBANGUNAN WADUK KUWIL DESA KAWANG-KOAN KABUPATEN MINAHASA UTARA - Alpriandi nFN; Lyndon Pangemanan; Vicki Moniaga (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This study aims to determine how the impact of the Kuwil reservoir development on the socio-economic community around the construction of the North Sumatra Minahasa District reservoir. This research was conducted in Kawangkoan Village from July to August 2018. The data used in this study are primary data and secondary data.Â Primary data obtained from respondents through surveys, documentation, interviews using a list of questions that have been prepared in advance, and secondary dataobtained from the local govemment. The results obtained from this study using the likert scale analysisshow the index of the contruction impact of the kuwil reservoir on the socio-economic community in Kawangkoan village, Kalawat District, North Minahasa Regency, located at 90.49% and categorized as Good.Keywords: Impact, socio-economic community, reservoir construction